2022
DOI: 10.1186/s12959-022-00381-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation and inflammatory biomarkers as predictors of venous thromboembolism in lymphoma patients

Abstract: Background Lymphomas are characterized by elevated synthesis of inflammatory soluble mediators that could trigger the development of venous thromboembolism (VTE). However, data on the relationship between specific immune dysregulation and VTE occurrence in patients with lymphoma are scarce. Therefore, this study aimed to assess the association between inflammatory markers and the risk of VTE development in patients with lymphoma. Methods The erythr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
(79 reference statements)
1
4
0
Order By: Relevance
“…The incidence of VTE in the present population at 9 months of follow-up was 8.5% and 12.5% in patients diagnosed with lymphoma and MM, respectively; these figures are consistent with the range reported in a recent review for the same follow-up period (20). This finding supports the observation that the highest incidence of VTE occurs within the first 3 months after cancer diagnosis [9,20,21], which can be attributed to the higher tumour burden and initiation of antineoplastic treatment [3,9]. Notably, all VTE events among patients with lymphoma occurred in patients diagnosed with aggressive lymphomas, as previously reported [22].…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of VTE in the present population at 9 months of follow-up was 8.5% and 12.5% in patients diagnosed with lymphoma and MM, respectively; these figures are consistent with the range reported in a recent review for the same follow-up period (20). This finding supports the observation that the highest incidence of VTE occurs within the first 3 months after cancer diagnosis [9,20,21], which can be attributed to the higher tumour burden and initiation of antineoplastic treatment [3,9]. Notably, all VTE events among patients with lymphoma occurred in patients diagnosed with aggressive lymphomas, as previously reported [22].…”
Section: Discussionsupporting
confidence: 92%
“…The present study found that PT levels≥11.45sec, Fbg levels≥3.33 g/L and TG levels≥1.37mmol/L were an independent risk factor for VTE in patients with lung cancer, with an OR of 2.15, 1.76 and 1.88, respectively. Currently, the association of inflammatory parameters(PLR and NLR) and the risk of thromboembolism has been attracted increasing interest in recent years ( 46 , 47 ). Based on the logistic regression analysis, our results showed that NLR at baseline were statistically significant in the univariate analysis, whereas elevated NLR were not associated with an increased risk of VTE in the multivariate analysis( P =0.381), which is partly compatible with the findings of more recent studies ( 46 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies demonstrated that SII did have a strong predictive value for VTE, while fundamental research provided theoretical support for the association of the inflammatory response with thrombosis [ 19 ]. Altered systemic inflammatory responses and active coagulation systems were encountered in patients with lung cancer, which were closely related to the development and progression of VTE [ 20 ].…”
Section: Discussionmentioning
confidence: 99%